Occurrence and Distribution of Microplastics in Soils and Intertidal Sediments at Fildes Bay, Maritime Antarctica - Perfetti-Bolaño, Alessandra; Araneda, Alberto; Muñoz, Katherine; Barra, Ricardo O. (Frontiers in Marine Science, 2022)
Increased human activity on the Antarctic Peninsula has generated microplastic contamination in marine systems; however, less attention has been paid to soils so far. We investigated the occurrence of microplastics in 11 surface soils and intertidal sediments collected from Fildes Bay, King George Island. A transect of soils at Antarctic stations until Fildes Bay was made (i.e., S1–S5). Intertidal sediments along the shore (i.e., IS1–IS5) and a reference sample from Ardley Island (i.e., IS6) were also collected. All samples were stored at 4°C and analyzed for the organic matter content, particle size, and pH. Plastic particles were counted and classified by shape using metal dissecting forceps and a stereomicroscope and further analyzed by Fourier-transform infrared spectroscopy (FT-IR). They were classified by length as fibers (length: 500–2,000 μm) and fragments (length: 20–500 μm). In soil, fragments reached an average of 13.6 particles/50 ml sample, while in intertidal sediments, no fragments were found, but a fiber abundance of 1.5 particles/50 ml sample was observed. The principal component analysis shows a relationship between fibers and intertidal sediments, whereas fragments present a relationship with soils. There were differences between the numbers of fragments found in soils and intertidal sediments (p = 0.003), with a high abundance of fragments at site S5, but no significant differences were observed for fibers. The physicochemical soil analysis revealed that larger particle sizes were observed in intertidal sediments (average = 706.94 ± 230.51 μm) than in soils (p = 0.0007). The organic matter content was higher in soil than in intertidal sediments (p = 0.006) reaching an average of 6.0%. Plastic fragments and organic matter were significantly correlated (r = 0.779, p = 0.005), while fibers were positively correlated with particle size (r = 0.713, p = 0.014). The fragments were composed of phenoxy resin with the same appearance, shape, and bright orange color as the coatings of the facilities. According to the FT-IR analysis, the fibers had different colors and were composed of polyethylene terephthalate (PET). Cotton was also present at the sites surrounding the sampling site close to the base effluent. The presence of fiber on Ardley Island (i.e., control) may indicate that microplastic contamination has reached protected areas. This is the first study to confirm the presence of plastic debris in Antarctic soils. Further studies should focus on the identification of plastic sources and on the management of human activities and their eventual effects on biota.